Degradation of mitochondrial DNA in cryoprotectant-treated hard coral (Echinopora spp.) oocytes. (June 2015) - Tsai, Sujune; Chen, Jiann-Chu; Spikings, Emma; Li, Jan-Jung; Lin, Chiahsin
Abstract A critical step for successful cryopreservation is to determine the optimal cryoprotectant treatment that can provide protective effects against cryoinjury during freezing and with minimal toxicity. Most cryoprotectants have chemical and osmotic effects when used at high concentrations. Cryoprotectants can damage coral mitochondrial distributions and membrane potentials, which results in reduced ATP production. As mitochondrial DNA (mtDNA) encodes for components of the electron transport chain (ETC) and plays a critical role in ATP synthesis capacity, we determined the effects of cryoprotectants on mtDNA in hard coral (Echinopora spp.) oocytes using quantitative real-time PCR. Our results showed that an insult from a cryoprotectant may be compensated for by the genetic defense mechanisms of these cells. Methanol was found to have the least effect on coral oocytes with regard to their energy status. A single oocyte without cryoprotectant treatment produced an average of 4, 220, 645 ± 169, 990 mtDNA copies, which was greater than that in mammals. However, relatively lower mtDNA copy numbers (<2, 000, 000) were observed when oocytes were treated with dimethyl sulfoxide (DMSO), propylene glycol (PG), ethylene glycol (EG), or glycerol at a concentration of 3 M for 20 min. These results provide direct evidence that hard coral (Echinopora spp.) oocytes are extremely susceptible to cryoprotectants and support the concerns with regard to the adverse effects of cryoprotectants.